Talent Management Analysis of Brilio.net - Camila Isabel De Sequera Lastrilla (Sekolah Tinggi Manajemen IPMI, 2022)
One of the rapidly expanding emergent digital sectors is Indonesia's digital media market. The ecosystem of numerous different businesses using digital media for commerce has grown to be very complex. Finding and keeping competent workers is crucial for businesses in the Media & Entertainment, Telecommunications, and Technology (TMT) sector to seize development prospects. In order to provide alternative media options for the younger population, Brilio was founded in March 2015. The present issues in the digital media ecosystem affect Brilio as a digital media company. These difficulties include the struggle to find and keep qualified and skilled talent. Online qualitative interviews served as the main technique of data gathering for this study. Three qualitative data points were primarily collected during the interview. The researchers started by gathering descriptive data regarding Brilio's current talent acquisition procedure and tools. Second, the researchers gathered information about the problems and difficulties Brilio has been experiencing. Finally, the researchers gathered information on the business's short- and long-term talent acquisition plans. The outcomes were put to use to establish adaptable long-term and short-term strategies to not only hire the best employees for their organization but also to build a skilled and qualified talent pool.